The Effect of Leverage and Good Corporate Governance on Sustainability Report Disclosure - Susilawati; Sri Ambarwati; Roy Prakoso (GoAcademica Research & Publishing, 2022)
The objective of this study was to examine the impact of leverage and good corporate governance on the disclosure of a company's sustainability report. This study employs quantitative methods. This study utilizes secondary data, specifically annual reports and sustainability reports or Sustainability Reports of banking businesses listed in BUKU 2, both of which were listed on the Indonesia Stock Exchange (IDX) during the period of 2020-2021. This study employed descriptive statistical tests, classical assumption tests including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests, and hypothesis testing including coefficient of determination test, f test, and t-test. The analytical tool used in this study is the SPSS 2.6 application. The results of this study indicate that Leverage, the Number of Boards of Commissioners, and the Number of Audit Committees do not influence the disclosure of sustainability reports in the banking industry listed in BUKU 2. At the same time, the proportion of Independent Commissioners affects the disclosure of sustainability reports in the banking industry listed in BUKU 2. Furthermore, the results of simultaneous calculations show that the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), the Board of Commissioners, the Independent Board of Commissioners, the Audit Committee and Total Assets simultaneously (simultaneously) have a significant effect on the disclosure of the sustainability report as well as the regression equation used in this study is reliable.